1989
DOI: 10.1135/cccc19893294
|View full text |Cite
|
Sign up to set email alerts
|

Potential antidepressants: 2-(Methoxy- and hydroxyphenylthio)benzylamines as selective inhibitors of 5-hydroxytryptamine re-uptake in the brain

Abstract: ChemInform Abstract A large variety of title compounds such as (VI) and (VIII) are synthesized using reaction sequences generally exemplified in the scheme for (VI). Some of the 2-(methoxy-and hydroxy-phenylthio)benzylamines prepared, especially compounds (VIIIa), indicate properties of potential antidepressants being highly active and selective inhibitors of 5-hydroxytryptamine reuptake in the brain structures and having the typical antireserpine activity. The most interesting compound of the series is (VI) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…After the solvent was evaporated, the crude product was purified by flash chromatography (EtOAc/petroleum ether/ Et3N: 4/5/1 for N,N-dimethyl derivatives and EtOAc/MeOH/ Et3N: 8/1/1 for N-methyl derivatives). 11), 293 (12), 291 (15), 227 (25), 197 (21), 165 (22), 164 (20), 132 (26), 58 (62), 46 (100), 42 (27). Anal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the solvent was evaporated, the crude product was purified by flash chromatography (EtOAc/petroleum ether/ Et3N: 4/5/1 for N,N-dimethyl derivatives and EtOAc/MeOH/ Et3N: 8/1/1 for N-methyl derivatives). 11), 293 (12), 291 (15), 227 (25), 197 (21), 165 (22), 164 (20), 132 (26), 58 (62), 46 (100), 42 (27). Anal.…”
Section: Methodsmentioning
confidence: 99%
“…Anal. (C15H17BrN2S) C, H, N. 4), 212 (19), 152 (11), 151 (42), 150 (26), 120 (100), 118 (25), 44 (29). Anal.…”
Section: Nn-dimethyl-2-(2′-amino-4′-bromophenylthio)benzylamine (8a)mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the compound 13a derivatives depicted in Scheme was performed following a five-step reaction pathway. Coupling of commercially available 2-mercaptobenzoic acid with acyl halides yielded compounds 21a – 21d according to the known literature and successively reacted with oxalyl dichloride in the presence of DMF to give the aroyl chloride; the resultant 22a – 22d were then reacted with N 1 , N 1 -dimethylethane-1,2-diamine to generate the target 23a – 23d analogues by amidation reaction under standard conditions with good yield. Sodium tetrahydroborate, boron trifluoride diethyl etherate was used to reduce 23a – 23d analogues to obtain the target 24a – 24d analogues in tetrahydrofuran.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…A novel radioiodinated SERT radiotracer for SPECT imaging, [ 123 I]IDAM, has been described recently which was based on the 2-(phenylthio)araalkylamine structure, originally developed as nontricyclic antidepressants. [12][13][14] IDAM was shown to have high specificity and selectivity for SERT in vitro and ex vivo in rat biodistribution studies, 15 while SPECT studies on baboons using [ 123 I]IDAM demonstrated that a transient equilibrium was quickly reached with midbrain-to-cerebellum ratios of 1.8:1 obtained at 120 min postinjection. 16 Recently we reported the radiosynthesis of a 11 Clabeled potential SERT ligand in the 2-(phenylthio)-araalkylamines series (5-trifluoromethyl-2-(2-dimethylaminomethylphenylsulfanyl)phenylamine) and showed that it readily crossed the blood-brain barrier (BBB).…”
Section: Introductionmentioning
confidence: 99%